Stuck on fast forward : youth with attention-deficit/hyperactivity disorder - Brinkerhoff, Shirley (Broomall, Pa. : Mason Crest Publishers, 2004)
Describes the effects of ADHD, both on the child and the caregiver, and explains how this controversial condition is diagnosed and offers treatment options.
Getting to know Connor -- Embarrassment -- Disaster -- Totally black -- Finding answers -- Changes -- Acceptance -- Hope.
Includes bibliographical references (p. 120-121) and index.
Keywords: Attention-deficit hyperactivity disorder -- Juvenile literature; Attention-deficit hyperactivity disorder